2018
DOI: 10.6061/clinics/2018/e244
|View full text |Cite
|
Sign up to set email alerts
|

UNIFESP Info Plastica – An informative application covering the most frequently performed plastic surgeries worldwide

Abstract: OBJECTIVES:The objective of this study was to develop a free smartphone application with reliable and useful information for the lay public on the most frequently performed plastic surgeries worldwide.METHODS:The five most frequently performed surgeries worldwide according to ISAPS (International Society of Aesthetic Plastic Surgery) were selected. Information from the websites of the American Society of Plastic Surgeons (ASPS), American Society for Aesthetic Plastic Surgery (ASAPS) and Brazilian Society of Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Upon review of the references within the 19 articles, an additional article was found to meet inclusion criteria, bringing the number of total articles included to 20. 9 Categorization by article type is as follows: app design and integration, 10–14 app store review, 4,15–17 interventional study with control group, 9,18–20 clinical case series, 21–24 and nonclinical case series of trainees. 25–27 Of the four interventional studies with control groups, two explicitly used randomization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon review of the references within the 19 articles, an additional article was found to meet inclusion criteria, bringing the number of total articles included to 20. 9 Categorization by article type is as follows: app design and integration, 10–14 app store review, 4,15–17 interventional study with control group, 9,18–20 clinical case series, 21–24 and nonclinical case series of trainees. 25–27 Of the four interventional studies with control groups, two explicitly used randomization.…”
Section: Resultsmentioning
confidence: 99%
“…This has traditionally been achieved through in-office consultations, printed materials, and online resources; however, Carvalho et al designed a mobile application to supplement the consent process, making this information more accessible to patients. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation